CERTAIN ASPECTS OF THE POSITIVE IMAGE OF THE SOCIAL SUPPORT OFFICER - Bespalko, Andrii (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . Positive image is an important element of professional functioning, development and formation of an employee of a certain field of activity as an individual and a subject of professional activity, contributes to the optimization of professional and human qualities. The formation of a positive image is a long-term and complex process that is formed under the influence of numerous factors and consists of many components. It should be noted that only constructive interaction of fundamental components is the key to acquiring a positive professional image. The purpose of the article is to study the theoretical provisions of image formation, the definition of external and internal components, which are integral components of the structure of a positive image of a social support officer. M e t h o d s . The following methods were used in the research process: analysis, generalization, comparison, systematization of scientific sources on the problem of research – formation of a positive image. R e s u l t s . The essence and content of the concepts of "image" and "positive image" were determined, and the main structural components were singled out. It was established that the positive professional image of a social support officer includes the following measurements: internal attitudes, the level of motivation and personal readiness of representatives of the sphere of social services provision; the idea formed in the mass consciousness about the necessity and social importance of social work as a type of professional activity and the personal characteristics of the representatives of the system of social support for the personnel of the Armed Forces of Ukraine; level of professional competence, professional system of values and norms of behavior, professional culture of representatives of the system of providing social services. C o n c l u s i o n s . During the formation of a positive image of the social support officer, one should rely on the quality of social services provided; presence of positive personal qualities and professional competence of social service providers. Concentration on one of the components of the image will not give a positive result. Only complex and systematic work will contribute to the formation and formation of a positive image of both the individual social support officer and the social work system in the Armed Forces of Ukraine in general.